Enzymolysis-based ultrasound extraction and antioxidant activities of polyprenol lipids from Ginkgo biloba leaves. Issue 3 (March 2016) - Zhang, Chang-Wei; Wang, Cheng-Zhang; Tao, Ran; Fang, Chuanjie
Graphical abstract: Highlights: The enzymolysis-assisted ultrasound extraction process of Ginkgo biloba leaf (GBL) polyprenols was optimized. The antioxidant activities of GBL lipids with different polar fractions was evaluated. The antioxidant ability of GBL lipids depends on the concentration of polyprenols. Abstract: Polyprenols are one of the most important lipid components in Ginkgo biloba leaves (GBLs). In this study, an enzymolysis-based ultrasound extraction procedure of GBL polyprenol (GBP) lipids was established, and the antioxidant activities of polyprenols and six kinds of polar fractions separated from GBL lipids via an optimal extraction procedure were studied. The results showed that the optimum conditions were an enzyme quantity of 0.5 g (the mass ratio of cellulase and pectinase was 1:2, and the enzyme activity was 60 U/mg), enzymolysis pH of 4.5, and temperature of ultrasound of 45 °C. Under these conditions, the yield of polyprenols was 0.80% ± 0.22%, which is 69.70% higher than that obtained by direct petroleum ether extraction. In addition, concentration c (content of polyprenols was 91.53%), fraction 3 (content of polyprenols was 43.28%), polyprenols (content of polyprenols >99%), and fraction 3 showed the strongest scavenging effect on DPPH (2, 2-diphenyl-1-picrylhydrazyl), ABTS (2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)), superoxide anion, and hydroxyl radicals with the corresponding IC50 values of 236.9, 76.84, 80.23, and 113.9 μg/mL. It is inferred that GBL lipids with different concentrations of polyprenols could play different roles in the research and development of cosmetics and functional food.